2008
DOI: 10.1007/s00125-008-0926-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the TCF7L2, CDKAL1 and SLC30A8 genes are associated with impaired proinsulin conversion

Abstract: Aims/hypothesis Variation within six novel genetic loci has been reported to confer risk of type 2 diabetes and may be associated with beta cell dysfunction. We investigated whether these polymorphisms are also associated with impaired proinsulin to insulin conversion. Methods We genotyped 1,065 German participants for single nucleotide polymorphisms rs7903146 in TCF7L2, rs7754840 in CDKAL1, rs7923837 and rs1111875 in HHEX, rs13266634 in SLC30A8, rs10811661 in CDKN2A/B and rs4402960 in IGF2BP2. All participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
181
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(204 citation statements)
references
References 15 publications
16
181
3
4
Order By: Relevance
“…Possession of the risk variant of rs13266634 is associated with a 17% increase in disease risk per allele [65]. R325 allele carriers also present an increased proinsulin:insulin ratio during an oral glucose tolerance test [66], an impaired insulin secretion during an intravenous glucose tolerance test [67] and lower β cell function (HOMA-B assessment) [68].…”
Section: Znt8 and T2d: Gwas Studiesmentioning
confidence: 99%
“…Possession of the risk variant of rs13266634 is associated with a 17% increase in disease risk per allele [65]. R325 allele carriers also present an increased proinsulin:insulin ratio during an oral glucose tolerance test [66], an impaired insulin secretion during an intravenous glucose tolerance test [67] and lower β cell function (HOMA-B assessment) [68].…”
Section: Znt8 and T2d: Gwas Studiesmentioning
confidence: 99%
“…Several studies have also indicated that rs7903146 affects insulin production in type 2 diabetes through reducing the conversion of proinsulin to insulin. These studies in fact support the close relationship between rs7903146 and damaged conversion of proinsulin to insulin (37,45). Genetic variations of rs7903146 are located in the non-coding region, and similar to other type 2 diabetes-related variants, it seems that their impact on the disease occurs through changes in gene expression.…”
Section: Discussionmentioning
confidence: 53%
“…Among variants of TCF7L2, rs7903146 T-allele is one of the most important genetic risk factors for T2D (36) and has been reported to have a strong direct relationship with T2D in different populations (12). This relationship is associated with defects in insulin production, and it is represented by reducing the release of insulin from pancreatic beta cells (37,38). Other studies have reported the association between rs7903146 T-allele with impaired glucose tolerance (34,38,39), increased birth weight (40), and increased anthropometric indices which show the role of the TCF7L2 phenotype in several tissues (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Эти данные были подтверждены на множественных этнических исследованиях европейских [8 13], азиатских [14 16], афро ка рибской [17] [10,19]. Также была обнаружена ас социация данных маркеров с повышенным уровнем проинсулина при одновременном сок ращении амплитуды инсулинового ответа в от вет на стимуляцию глюкозой [20], низкой секре цией инсулина [21,22] и уменьшением скорости превращения проинсулина в инсулин [23].…”
Section: Association Of the Polymorphisms Of The Tcf7l2 Genes With Tyunclassified